Platformed intimacies: Professional belonging on social media - Soronen Anne; Koivunen Anu (Sage, 2025)
This article explores how social media presence and platform engagements inform and affect creative workers' sense of professional agency and craft. Focusing on Finnish theatre, film and TV actors' perceptions of their social media interactions, the article proposes the concept of platformed intimacy to capture the simultaneous importance and ambivalence of mobile attachments that characterise actors' platformed lives. The research participants consisted of 15 freelancers and theatre employees, aged between 29 and 64 years. The analysis was based on the diary-interview method and close reading. In this article, we suggest that to understand the complexities involved in creative workers' presence on social media platforms, it is important to broaden the investigation from self-promotion to questions of professional identities and communities. The concept of platformed intimacy captures how actors experience social network sites and apps, such as Instagram and Facebook, as 'grey areas' in which they deal with the frequent uncertainty about the meaning of social media visibility for their employability and future collaborations. For actors in our study, social media presence is intimately entangled with their sense of professionalism and desire of to belong to a professional community of peers. As such it articulates senses of proximity and reciprocity as well as feelings of discomfort and anxiety.